IN SILICO STUDY OF THE POTENTIAL OF GAMBIR LEAF CATECIN COMPOUNDS (Camellia sinensis L.) AS ANTI-BACTERIAL AGAINST Mycobacterium tuberculosis IN InHA - Riska Luthfiani (Universitas STRADA Indonesia, 2019)
Isoniazid is an anti-tuberculosis pro-drug by inhibiting mycolic acid in bacterial cell walls which requires activation by inhA and the presence of mutations in the Kat-G gene increases resistance to isoniazid. The disadvantages is that high humidity can cause bacteria to grow quickly. Pathogenic bacteria are one of the causes of infection, both gram-positive bacteria and gram-negative bacteria. One of the diseases caused by bacteria is tuberculosis, which is caused by Mycobacterium tuberculosis. The four compounds of the catechin group from gambir plants, namely Epikatekin (EC), Epigallo catechin (EGC), Epikatekin gallate (ECG), and Epigallokatekin gallate (EGCG), three of which meet the criteria of Lipinski's five laws, namely in EC, ECG and EGC with one violation, namely Hydrogen Bond Donor> 5 where Lipinski's criteria for compounds are said to be good if HBD < 5